Study into blood pressure measurements using a pulse oximeter - Yeh, Tzu Wei (2017)
Pulse oximeter signal provides information regarding pulse rate and blood oxygen concentration. It is also proposed for the possibility of Blood Pressure measurements. The purpose of this study was to investigate whether an existing pulse oximeter can be used for obtaining signals and evaluating blood pressure. The algorithm for calculating the blood pressure was suggested using pulse transit time (PTT) and peak-to-peak time (PPT) to observe the changes of blood pressure and analysis the correlation between blood pressure respectively. This project involved to collected the datasets for Electrocardiogram (ECG), Photoplethysmogram (PPG) and blood pressure. These datasets were obtained from the 32 patients in the hospital by PhD student David Liu. ECG and PPG waveform are plotted in the same diagram through Matlab. It is convenient to calculated the PPT and PTT value. The changes of blood pressure are visible in the graph. From this calculation, the relationship between blood pressure and PPT and PTT can be found.